Psychological Variables Associated With Post-Traumatic Stress Disorder in Firefighters: A Systematic Review - Serrano Ibáñez, Elena R.; Corrás, Tania; del Prado, Mirtha; Diz-Casal, Javier; Varela, Carmen (My University, 2025)
Firefighters are repeatedly exposed to work-related potential traumatic events and have an increased risk of developing post-traumatic stress disorder (PTSD). However, the mechanisms implicated in this relationship are not clear. The aim of this study was to analyse the risk and protective factors related to the development of PTSD in firefighters. According to PRISMA, a systematic review of scientific literature was conducted in Web of Science, PsycINFO, Scopus, PubMed and the Cochrane Central Register of Controlled Trials. Quality in Prognosis Studies (QUIPS) was used as the methodological quality indicator of the selected articles (PROSPERO reference CRD42020213009). Prognostic studies involving active firefighters with presence of post-traumatic symptomatology, presenting original findings, and written in Spanish or English were included. A total of 1768 potentially eligible articles were identified. According to the inclusion criteria, 87 articles were selected to evaluate the full text. Finally, 19 articles were included, comprising 12,298 active firefighters. There is high heterogeneity in the variables evaluated in the different studies. Taking the data for which this review has found more evidence (moderate support), operational stress, job duration, burnout, expressive suppression and rumination could be risk factors of PTSD, and belongingness and dispositional mindfulness could be protective factors. Other variables with weak support (e.g. resilience) were analysed. This review analyses the available literature, highlighting its scarcity for future research on the subject. Due to repeated trauma exposure, it is important to continue investigations and bear these variables in mind for the prevention of PTSD in firefighters. Keywords post-traumatic stress disorder, firefighters, risk factor, protective factor, review